Case Report: Synucleinopathy Associated With Phalaris Neurotoxicity in Sheep - Tayebi, Mourad; Pinczowski, Pedro; Habiba, Umma; Khan, Rizwan; David, Monique A.; Summers, Brian A. (Frontiers in Veterinary Science, 2021)
Chronic intoxication with tryptamine-alkaloid-rich phalaris species (spp) pasture plants is known colloquially as phalaris staggers syndrome, a widely occurring neurological disorder of sheep, cattle, horses and kangaroos. Of comparative interest, structurally analogous tryptamine-alkaloids cause experimental Parkinsonism in primates. The aim of this study was to investigate the neuropathological changes associated with spontaneous cases of phalaris staggers in sheep with respect to those encountered in human synucleinoathy. In sheep affected with phalaris staggers, histological, immunohistochemical and immunofluorescence analysis revealed significant accumulation of neuromelanin and aggregated α-synuclein in the perikaryon of neurons in cerebral cortex, thalamus, brainstem, and spinal cord. Neuronal intracytoplasmic Lewy bodies inclusions were not observed in these cases of ovine phalaris staggers. These important findings established a clear link between synucleinopathy and the neurologic form of phalaris plant poisoning in sheep, demonstrated in 6 out of 6 affected sheep. Synucleinopathy is a feature of a number of progressive and fatal neurodegenerative disorders of man and may be a common endpoint of such disorders, which in a variety of ways perturb neuronal function. However whether primary to the degenerative process or a consequence of it awaits clarification in an appropriate model system.